Pengembangan Sistem Penilaian Kenaikan Pangkat Perawat Rumah Sakit (Studi Kasus : Rumah Sakit Islam Faisal Makassar) - Meidita Famirah; Achmad Arwan; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Faisal Islamic Hospital Makassar is a type B hospital located in the city of Makassar. Faisal Makassar Islamic hospital has 22 facilities, 12 health services and is supported by 227 nurses in running the health service. to maximize health services, quality of nurses and improve the quality of nursing Faisal Islamic hospitals, then nurses are managed with activities in the valuation of promotion. The promotion of nurses is done to know the results of the achievements of nurses in service, nurses perfomances in service and to raise wages and nurse allowance. Rank valuation is done by collecting credit numbers and documents of nurse work will be accumulated in assessment activities carry out manually. the head of nurses and human resources at the Faisal Islamic Hospital assessed that the assessment activities carried out were still not effective, In activities, there are often errors in the data on the work of nurses that are not measured and the slowness in the process of accumulating credit and documents on the results of nurses' work. The development of a rank valuation management system is expected in solving problems by using web-based technology in system creation. The research was conducted by knowing the needs of the system, system design and implementation of web-based systems with waterfall methods. there are 3 actors in the role and 56 functional ones that will be tested on unit testing, integration, validation and compatibility. the test results show the level of testing is 100% successful and valid.